Civiltà del legno: il monastero - Galetti, Paola (Hortus Artium Medievalium, 2017)
Abstract The contribution would like to offer some reflections on use of wood in the monastic building structures, considering both written and archaeological sources. Attention is particularly directed to the articulation of the monastic space, to constructive activities and to material culture.